Pengaruh Implementasi Pendidikan Kewarganegaraan terhadap Moralitas Mahasiswa di Universitas Pohuwato - Mohamad Akuba; Fibriyanti Karim (Journal on Education, 2024)
Students' understanding of civic values taught in Civic Education (Civics Education) is still low. Although Civics Education has become a compulsory course, many students do not understand or internalize values such as integrity, social responsibility, and concern for the community. The purpose of the study was to determine the effect of the implementation of civic education on student morality at Pohuwato University. This research uses quantitative methods with regression analysis. The results explained that the regression analysis showed that the effect of the implementation of civic education on student morality at Pohuwato University was 1.031, which means that indeed the implementation of civic education has a significant effect on student morality at Pohuwato University. The importance of this research is that the theory received by students can have an impact and influence on morality so as to produce a directed and sustainable generation.